Large-scale soil erosion performance test of water hyacinth limited life geosynthetics combined with Ruzi grasses. Issue 3 (July 2014) - Tanchaisawat, T.; Bergado, D. T.; Artidteang, S.
Abstract : First, the performance of woven water hyacinth limited life geosynthetics (LLGs) was investigated in the laboratory using index and hydraulic tests. Second, the field soil erosion control tests were conducted to confirm the performance of woven water hyacinth LLGs with and without vegetation using artificial rainfall. The average flow rate from the permittivity test on woven water hyacinth LLGs increased with higher hydraulic gradient while the transmissivity values decreased at higher normal pressures. From laboratory test results, woven water hyacinth LLGs can be utilized for erosion control in field applications because the moisture retained in woven water hyacinth was high thus it can help the growth of vegetation. In the full scale field erosion control test, the surface runoff was reduced when using woven water hyacinth cover combined with Ruzi grass which was further reduced with increasing growing periods. The soil loss was lowest when combining Ruzi grass with woven water hyacinth. Therefore, woven water hyacinth can be used effectively to control soil erosion and can be enhanced by using in combination with vegetation. In the absence of vegetation, the smaller opening size of woven water hyacinth LLGs with 8×8 mm has better erosion resistance than the larger opening size of 12×12 mm when runoffs were similar for both opening sizes. The results also indicated that using woven water hyacinth with increasing growing period of Ruzi grass the soil loss was greatly reduced. Finally, it can be concluded that for soil erosion control, water hyacinth LLGs combined with Ruzi grass can be applied in sloping ground surface.